Bisphosphonates for prevention of bone loss in women with early breast cancer - Tsoi, Daphne (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the efficacy and safety of bisphosphonates for the prevention of bone loss caused by cancer treatment in women with early breast cancer.